(untitled) (Jurnal Simki Economic, 2023)
The capital market itself plays a strategic role in increasing a country’s economic resilience. This inevitably wants to get used to investors’ investment in the capital market, exclusively stocks. The stock price that compares the growth of all stocks listed on the Indonesia Stock Exchange is the Composite Stock Price Index. The growth of stock price movements is not always stable, but there will be changes that are intertwined in stock prices either up or down, it will certainly affect the movement of the composite stock price index (JCI). This study aims to identify and analyze the factors influencing the Indonesia Composite Stock Price Index. Quantitative type of research, using secondary data based on time series time horizons and cross section data for the period January 2017 to December 2021 obtained from official websites such as Bank Indonesia and BPS. This study used the Autoregressive Distributed Lag (ARDL) model. The results of the study using the ARDL method showed that the simultaneous regression test (Test F) showed that the four independent variables in the study together had an influence on the Composite Stock Price Index. Meanwhile, in the partial regression test (Test t) it can be stated that the variables interest rate and JUB have a positive and significant influence on the JCI Meanwhile, the inflation and exchange rate variables have a negative and significant influence on the JCI.